(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The antimicrobial activity of Kalanchoe pinnata (Syn Bryophyllum pinnatum) against clinical pathogen is well documented in literature but there is paucity of information on its effect against plant pathogens. This work attempts to evaluate inhibitory activity of Kalanchoe pinnata (Syn Bryophyllum pinnatum) on selected plant pathogens. Aqueous, acetone, ethanol and methanol leaf, stem and root extracts of Kalanchoe pinnata (Syn Bryophyllum pinnatum) were prepared using standard techniques. Extracts were tested against bacteria and fungi isolated from some diseased plants, both singly and in combination with standard antimicrobials. Inhibitory activity was determined using agar well diffusion technique as well as broth dilution technique. Results indicate that the leaf ethanol extract was most effective against the plant pathogens. Zones of inhibition (mm) ranged from [19.0 Â± 0.32] for Aspergillus flavus to [23.5 Â± 0.22] for Xanthomonas campestris. Meanwhile, the Minimum inhibitory concentration (MIC) reduced from 6.25 mg/mL to 3.13 mg/mL (for Xanthomonas oryzae and Xanthomonas campestris) when leaf extract was used in combination with streptomycin. Furthermore, MIC reduced from 1.56 mg/mL to 0.78 mg/mL (for Aspergillus flavus and Aspergillus niger) when extract was used in combination with cycloheximide. Ethanol leaf extract of Kalanchoe pinnata (Syn Bryophyllum pinnatum) was most effective against selected plant pathogens. Also, effectiveness of extract was enhanced when used in combination with regular antimicrobial. Kalanchoe pinnata (Syn Bryophyllum pinnatum) may become useful as a biological control agent for plant disease pathogens